Determinant of Indonesian Manufacturing Output - Dhina, Arga Prati; Wasiaturrahma, Wasiaturrahma (Journal of Developing Economies, 2018)
The role of manufacture in Indonesia influence the economic growth. This research aims to observe and analyze influencing factors of manufacturing sector output in Indonesia. The research method used Error Correction Model (ECM) at period 2005 in 1stquartal – 2017 in 4thquartal. This research used secondary data from Statistik Ekonomi dan Keuangan Indonesia (SEKI) and Federal Reserves. The results of the study show that in long term estimation lend interest rate and inflation have negative and significant impact, whereas FDI has positive and significant impact towards manufacturing sector output. Otherwise, in short term estimation show that lend interest rate has negative and significant impact, while inflation and FDI have no significant impact towards manufacturing sector output.   Keywords: ECM, real exchange rate rupiah/USD, inflation, lend interest rate, FDI, manufacturing sector output